Mixing unfamiliar lambs upon arrival at the abattoir affects their social behavior and meat traits - Ithurralde, Javier; Ungerfeld, Rodolfo; Maurina, Geisibel Aparecida De Mello; Figueiró, Giuliano Moraes; Cabrera, María Cristina; Freitas-de-Melo, Aline (Frontiers in Animal Science, 2025)
The aim of the study was to determine the effects of mixing unfamiliar lambs when they arrive at the abattoir 28-29 h before slaughtering on social behavior and meat quality. Forty Texel x Corriedale male lambs were transported together in the same truck for 5 h to a slaughterhouse where they were separated into two experimental groups homogeneous according their body weight: twenty lambs were allocated in a single resting pen (1.13 m2/animal) together with other ten familiar male lambs (CON group), while other twenty lambs were allocated together in a resting pen with similar characteristics, but mixed with ten resident unfamiliar male lambs (MIX group). Animals were kept in the resting pens for 28-29 h before slaughter and were slaughtered on the same day following standard procedures. Lambs’ behavior was recorded during the premortem period. The longissimus thoracis muscle pH, and temperature were recorded 45 min and 24 h after slaughter. Meat traits were measured in 24-h and 7-day-aged meat from the longissimus lumborum muscle. The MIX lambs displayed a greater number of both sexual behaviors and the sum of agonistic and sexual behaviors than the CON lambs (P < 0.001 for all). The MIX lambs had lower carcass pH (P = 0.04) and temperature (P < 0.001), and meat was lighter (P = 0.016), redder (higher a* values; P = 0.003) and more tender (lower Warner Bratzler shear force values; P = 0.048) than those from CON lambs. The MIX lambs tended to have more glycogen content than CON lambs (P= 0.057). However, no differences were detected regarding sarcomere length or lactate residual content. In summary, mixing unfamiliar eight-month-old male lambs during a 28-29 h resting period before slaughter affected the lambs’ social behavior and induced changes in meat quality. Lambs exposed to MIX treatment showed carcass with lower values of pH and temperature, meat lighter, redder, and more tender, with normal sarcomere lengths and residual lactate content. The findings of the present study have potential implications for lamb meat industry since they demonstrate that pre-slaughter social mixing affects animal welfare and induces changes in meat quality characteristics.